1986
DOI: 10.4141/cjas86-008
|View full text |Cite
|
Sign up to set email alerts
|

Serum Androgen and Gonadotropin Profiles Over the First Year of Life in Ram Lambs and the Effect of Season of Birth

Abstract: Coor, S. J. ,A.No RewLrNGS, N. C. 1986. Serum androgen and gonadotropin profiles over the first year of life in ram lambs and the effect of season of birth.Can. J. Anim. Sci. 662 6'7-75.Testosterone (T), dihydrotestosterone (DHT), androstenedione (D), androsterone (A), 5c-androstane-3a, l7p-diol (3a-diol), 5a-androstane-3B, 17p-diol (3p-diol), LH and FSH were measured in serum from rams over the first year of life. Marchborn rams had higher mean serum LH levels than July-born rams, but mean serum FSH levels w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In the present study, the age trends for LH pulse frequency and amplitude reflected those reported by Olster & Foster (1986 Cook & Rawlings (1986 Differences between treatment groups are significant: *P < 005 or **P < 001. Columns, within each treatment group, with different subscripts are significantly different (P < 005).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the present study, the age trends for LH pulse frequency and amplitude reflected those reported by Olster & Foster (1986 Cook & Rawlings (1986 Differences between treatment groups are significant: *P < 005 or **P < 001. Columns, within each treatment group, with different subscripts are significantly different (P < 005).…”
Section: Discussionsupporting
confidence: 59%
“…Serum testosterone concentrations were estimated for each lamb, at each treatment, on a serum pool of samples taken once an hour over the sampling periods. Serum concentrations of testosterone were determined in a previously validated radioimmunoassay (Cook & Rawlings, 1986), with samples batched for analysis as described for LH and FSH. Sensitivity was 003 ng/ml.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports on changes in circulating FSH in developing rams have generally depicted progres¬ sive elevations from birth to a maximum at about 5 to 9 weeks of age, followed by either a sharp or a gradual decline (Cook & Rawlings 1986, Yarney & Sanford 1989, Hochereau-de Reviers 1991.…”
Section: Discussionmentioning
confidence: 98%